Avançando na inclusão socioprodutiva: a convergência da economia da funcionalidade e da cooperação e inovação social em uma comunidade quilombola de Minas Gerais - Márcia Cristina Moreira Paranhos (2023)
The aim of this work is to promote the appreciation and recognition of traditional knowledge in quilombola communities through the application of the principles of the Economy of Functionality and Cooperation (EFC), in order to foster social innovation and promote socio-productive inclusion and entrepreneurship in traditional basis. The research was based on the hypothesis that EFC precepts have the potential to stimulate social innovation in traditional territories and provide more collaborative and cohesive social interactions between local actors. The objective of this investigation is to collaborate in the advancement of an experience of socio-productive inclusion in the quilombola community of Cachoeira dos Forros, located in the city of Passa Tempo in Minas Gerais, applying the principles of the Economy of Functionality and Cooperation. Quilombos represent a significant social legacy, the result of struggles and resistance against slavery imposed on black and indigenous people who participated in the formation of the Brazilian people. The social organization of these communities is based on family, cultural and historical ties, marked by cooperation, solidarity and resistance. The preservation of their traditions, customs and ancestral knowledge is essential for the maintenance of these communities, as well as guaranteeing the well-being and essential rights of their participants. In this area, it appears that the knowledge of its members can contribute to the sustainable management of ecosystems and the rational use of natural resources. It is therefore imperative to expand the forms of productive, economic and social inclusion of quilombola communities, reflecting on socio-environmental innovations related to their knowledge. Using an action research method anchored in the EFC approach, this study sought solutions to the challenges faced by the quilombola community of Cachoeira dos Forros/MG, based on cooperation between local actors. Seven steps were adopted to implement a sustainable development model based on the EFC: mapping of challenges, actors in the territory, joint reflection, financial sustainability, legal coherence, governance and development of intangible resources. When analyzing the social innovation model, based on the principles of EFC, strengths, opportunities for improvement and recommendations for actions were identified in each of these stages. Evidence of social innovation and benefits for the community are presented throughout the research, as well as an agenda of investigations for future studies. The results indicate that the adoption of EFC principles can contribute to local sustainable development, in addition to boosting social innovation in the territory, addressing community problems and promoting more collaborative and cohesive social relations between local actors.